CO2 conversion catalyst as well as preparation method and application thereof

By loading Ni nanoparticles and carbonic anhydrase on the UiO-66 metal organic framework, efficient catalysis of CO2 hydrogenation reaction and CO2 hydration reaction is achieved, solving the problems of low efficiency of existing catalysts and insufficient multi-path conversion capabilities, and having good stability and reusability.

CN119506256APending Publication Date: 2025-02-25ZHEJIANG FORESTRY UNIVERSITY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411589689.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing CO2 conversion catalysts can only solve the conversion of one pathway of CO2. The catalytic reaction efficiency is limited, and the multi-path conversion of CO2 cannot be achieved. There is a lack of catalysts with high repetition rate, long life and high catalytic reaction efficiency.

Method used

UiO-66 metal organic framework supports Ni nanoparticles and carbonic anhydrase, and the coupling of chemical catalysts and enzymes can achieve efficient catalysis of CO2 hydrogenation reaction and CO2 hydration reaction.

Benefits of technology

It realizes efficient catalysis of CO2 hydrogenation reaction and CO2 hydration reaction, has good long-term stability and reusability, and improves the overall performance of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506256A_ABST
    Figure CN119506256A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalysts and discloses a CO2 conversion catalyst as well as a preparation method and application thereof. The CO2 conversion catalyst is prepared from a UiO-66 metal organic framework, ni nano particles and carbonic anhydrase are loaded on the UiO-66 metal organic framework. The CO2 conversion catalyst provided by the invention can catalyze CO2 hydrogenation reaction and CO2 hydration reaction, can realize higher CO2 hydrogenation reaction efficiency and CO2 hydration reaction efficiency, and also has better long-term stability and reusability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalyst technology, and in particular to a CO2 conversion catalyst and a preparation method and application thereof. Background Art

[0002] CO2 emission reduction and high-value utilization have received unprecedented attention from the international community. Using cutting-edge catalytic chemistry technology to synthesize high-value-added products using CO2 as raw material is one of the important ways to achieve CO2 emission reduction. Many scientists use CO2 raw materials to conduct research on CO2 derivatization methods. In recent years, the preparation of methanol, formic acid and other products from CO2 has been industrialized, but due to the harsh reaction conditions, high temperature, high pressure and high-purity CO2 are required to obtain a better reaction. Therefore, the study of efficient and low-energy catalysts that can achieve this reaction under mild conditions has important application value.

[0003] At present, commonly used catalytic methods include biomimetic catalysis, thermal catalysis, electrocatalysis, enzyme catalysis, etc. However, existing catalysts can only solve the conversion of CO2 in a certain way, and the catalytic reaction efficiency is limited. No catalyst can convert CO2 in multiple ways. It is urgent to improve the CO2 conversion catalyst and find a catalyst that meets the requirements of high repeated use rate, long life and high catalytic reaction efficiency to achieve efficient activation and multi-path conversion of CO2. Therefore, it is of great significance to develop new catalysts for the catalytic conversion of CO2 to carbon dioxide. Summary of the invention

[0004] In order to solve the above technical problem, that is, the existing CO2 conversion catalyst can only solve the conversion of a certain pathway of CO2, and the catalytic reaction efficiency is limited, the present invention provides a CO2 conversion catalyst and its preparation method and application. The CO2 conversion catalyst can catalyze CO2 hydrogenation reaction and CO2 hydration reaction, and can achieve high CO2 hydrogenation reaction efficiency and CO2 hydration reaction efficiency, and also has good long-term stability and reusability.

[0005] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a CO2 conversion catalyst, comprising a UiO-66 metal organic framework; the UiO-66 metal organic framework is loaded with Ni nanoparticles and carbonic anhydrase.

[0006] The CO2 conversion catalyst of the present invention couples a chemical catalyst (Ni nanoparticles) with an enzyme (carbonic anhydrase) to achieve bifunctional catalysis, wherein the reactions catalyzed by the two active sites are as follows: (1) Chemical catalysts can catalyze CO2 hydrogenation reactions. Methanol synthesis and water-gas shift reaction are the two main competing reactions in the process of CO2 hydrogenation to methanol. The preferred pathway for CO2 hydrogenation is mainly determined by the ability of the catalyst to bind to key reaction intermediates. Dissociated H can bind to metal ions on the surface of the catalyst, which greatly promotes the process of binding to CO2 molecules. Due to the highly dispersed ultra-small nickel particles and the low apparent activation energy of the catalyst, the catalyst is more likely to obtain higher catalytic activity.

[0007] (2) Carbonic anhydrase can use CO2 as a substrate and efficiently catalyze the hydration reaction of CO2, accelerating the conversion of HCO3 - The formation of CO2 is then followed by the formation of CaCO3 through mineralization to solidify CO2. Compared with the physical and chemical capture of CO2 technology, the enzymatic reaction is efficient and specific, the reaction conditions are mild, and it is environmentally friendly.

[0008] The present invention selects specific chemical catalysts and enzymes and loads them on a specific metal organic framework (MOF). The three can cooperate with each other and promote each other in function, thereby improving the efficiency of the catalytic reaction, for example: (1) The basic unit of UiO-66 is Zr6O4(OH)4 octahedron, which forms a crystal by linking with twelve terephthalic acid ligands. After Ni nanoparticles are loaded on UiO-66, the interaction between the two can be utilized to improve the catalytic activity of the catalyst.

[0009] (2) Although carbonic anhydrase and Ni nanoparticles catalyze different reactions when used alone, the present invention finds that loading carbonic anhydrase onto Ni@UiO-66 (i.e., UiO-66 loaded with Ni nanoparticles) can improve the efficiency of Ni@UiO-66 in catalyzing CO2 hydrogenation reactions.

[0010] (3) Although the immobilization of the enzyme will reduce its degree of freedom and have an adverse effect on the catalytic activity, the present invention can improve the catalytic activity of carbonic anhydrase after loading it onto Ni@UiO-66, achieve a higher CO2 hydration reaction efficiency, and also improve its long-term stability and reusability, so that it can still maintain a high activity after long-term storage and multiple uses.

[0011] Based on the above effects, the CO2 conversion catalyst of the present invention is composed of a UiO-66 metal organic framework and Ni nanoparticles and carbonic anhydrase loaded thereon. When catalyzing CO2 conversion, this whole can achieve a higher CO2 hydrogenation reaction efficiency and a higher CO2 hydration reaction efficiency, and at the same time has good long-term stability and reusability.

[0012] Preferably, in the CO2 conversion catalyst, the loading amount of Ni nanoparticles is 15-20%, and the mass ratio of Ni nanoparticles to carbonic anhydrase is 1:2.0-2.9.

[0013] Based on the coordination relationship between Ni nanoparticles and carbonic anhydrase, the present invention team found that when the mass ratio of the two is controlled at 1:2.0-2.9, the efficiency of the CO2 hydrogenation reaction can be improved to a greater extent.

[0014] In a second aspect, the present invention provides a method for preparing the CO2 conversion catalyst, comprising the following steps: I: dissolving a nickel salt in water, adding a UiO-66 metal organic framework, combining, evaporating to remove water, and then reducing nickel ions to Ni to obtain UiO-66 loaded with Ni; II: Mix carbonic anhydrase, polyvinyl pyrrolidone and water to obtain enzyme solution, add the product of step I, combine them, and then separate the product.

[0015] Preferably, in step I, the specific process of reducing nickel ions to Ni includes: heating to 300-320° C. at a rate of 4-6° C. in an inert gas atmosphere and maintaining for 4.5-5 hours, then introducing a reducing gas containing hydrogen, and continuing to calcine at 250-300° C. for 5-5.5 hours.

[0016] Furthermore, the reducing gas is a mixture of hydrogen and argon, wherein the volume fraction of hydrogen is 3-5%.

[0017] Preferably, in step II, in the enzyme solution, the concentration of carbonic anhydrase is 10-15 mg / mL, and the concentration of polyvinyl pyrrolidone is 5-10 mg / mL.

[0018] Preferably, in step I, the combining method is stirring for 10 to 15 hours; in step II, the combining method is stirring for 5 to 10 minutes.

[0019] Preferably, in step I, the preparation step of the UiO-66 metal organic framework includes: dissolving a zirconium salt and terephthalic acid in a solvent, stirring at 20 to 30° C. for 1 to 1.5 hours, adding formic acid, continuing to stir for 0.5 to 1 hour, reacting at 115 to 125° C. for 20 to 30 hours, and separating the product; the mass volume ratio of the zirconium salt, terephthalic acid and formic acid is 1g: 0.5 to 0.8g: 100 to 150mL.

[0020] In a third aspect, the present invention provides an application of the CO2 conversion catalyst in a CO2 conversion reaction, wherein the products of the CO2 conversion reaction include methanol and carbonic acid.

[0021] Preferably, the CO2 conversion reaction is carried out in an electrolysis device, comprising the following steps: in the electrolysis device, a glass slide or carbon rod electrode is used as an anode, a glassy carbon electrode containing the CO2 conversion catalyst is used as a cathode, an Ag / AgCl composite electrode is used as a reference electrode, a bicarbonate solution is used as an electrolyte, CO2 is introduced into the electrolyte in the cathode area, and electricity is turned on to carry out the reaction.

[0022] Preferably, the CO2 conversion reaction is carried out in a vacuum reaction device, comprising the following steps: adding a dispersion containing the CO2 conversion catalyst and water into a closed vacuum reaction device, evacuating the device, heating to evaporate water, and introducing CO2 to react.

[0023] Furthermore, the dispersion is a mixture of a CO2 conversion catalyst, N-methyldiethanolamine and water.

[0024] Compared with the prior art, the present invention has the following advantages: (1) The present invention loads Ni nanoparticles and carbonic anhydrase on UiO-66. While playing their respective roles, the three can cooperate with each other and promote each other in function, so that the catalyst as a whole can achieve higher CO2 hydrogenation reaction efficiency and CO2 hydration reaction efficiency, while also having good long-term stability and reusability.

[0025] (2) In the CO2 conversion catalyst of the present invention, by controlling the ratio between Ni nanoparticles and carbonic anhydrase, the efficiency of catalyzing the CO2 hydrogenation reaction can be further improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Infrared spectra of UiO-66 and CA / Ni@UiO-66.

[0027] Figure 2 XRD crystal diffraction patterns of UiO-66 and CA / Ni@UiO-66.

[0028] Figure 3 XPS spectra of UiO-66 and CA / Ni@UiO-66.

[0029] Figure 4 Thermogravimetric curves of UiO-66 and CA / Ni@UiO-66.

[0030] Figure 5 Schematic diagram of the structure of an H-type electrolytic cell for CO2 hydrogenation reaction.

[0031] Figure 6The structure diagram of the CO2 hydration reaction device is shown in the figure. The accompanying drawings are marked as follows: 1. micro vacuum reactor; 2. magnetic stirrer; 3. gas outlet valve; 4. gas inlet valve; 5. vacuum pressure sensor; 6. vacuum pump; 7. high-purity carbon dioxide cylinder; 8. magnetic heating stirrer; 9. computer.

[0032] Figure 7 Comparison of the catalytic CO2 hydration reaction activities of free CA, pure UiO-66, and CA / Ni@UiO-66.

[0033] Figure 8 These are the long-term stability test results of free CA and CA / Ni@UiO-66 in 40℃ MDEA solution.

[0034] Fig. 9 The reusability test results of CA / Ni@UiO-66. DETAILED DESCRIPTION

[0035] The present invention will be further described below in conjunction with the embodiments.

[0036] Overall embodiment A CO2 conversion catalyst comprises a UiO-66 metal organic framework; the UiO-66 metal organic framework is loaded with Ni nanoparticles and carbonic anhydrase.

[0037] As a specific implementation, in the CO2 conversion catalyst, the loading amount of Ni nanoparticles is 15-20%, and the mass ratio of Ni nanoparticles to carbonic anhydrase is 1:2.0-2.9.

[0038] A method for preparing the CO2 conversion catalyst comprises the following steps: I: dissolving nickel salt in water, adding UiO-66 metal organic framework, combining, evaporating to remove water, and then reducing nickel ions to Ni to obtain UiO-66 loaded with Ni; II: Mix carbonic anhydrase, polyvinyl pyrrolidone and water to obtain enzyme solution, add the product of step I, combine them, and then separate the product.

[0039] As a specific implementation, in step I, the specific process of reducing nickel ions to Ni includes: heating to 300-320°C at a rate of 4-6°C in an inert gas atmosphere and maintaining for 4.5-5h, then introducing a reducing gas containing hydrogen, and continuing to calcine at 250-300°C for 5-5.5h; the reducing gas is a mixture of hydrogen and argon, wherein the volume fraction of hydrogen is 3-5%.

[0040] As a specific implementation, in step II, in the enzyme solution, the concentration of carbonic anhydrase is 10-15 mg / mL, and the concentration of polyvinyl pyrrolidone is 5-10 mg / mL.

[0041] As a specific implementation manner, in step I, the combining method is stirring for 10 to 15 hours; in step II, the combining method is stirring for 5 to 10 minutes.

[0042] As a specific implementation method, in step I, the preparation step of the UiO-66 metal organic framework includes: dissolving a zirconium salt and terephthalic acid in a solvent, stirring at 20 to 30° C. for 1 to 1.5 hours, adding formic acid, continuing to stir for 0.5 to 1 hour, reacting at 115 to 125° C. for 20 to 30 hours, and separating the product; the mass volume ratio of the zirconium salt, terephthalic acid and formic acid is 1g: 0.5 to 0.8g: 100 to 150mL.

[0043] The CO2 conversion catalyst is used in a CO2 conversion reaction, and the products of the CO2 conversion reaction include methanol and carbonic acid.

[0044] As a specific implementation manner, the CO2 conversion reaction is carried out in an electrolysis device, including the following steps: in the electrolysis device, a glass slide or carbon rod electrode is used as an anode, a glassy carbon electrode containing the CO2 conversion catalyst is used as a cathode, an Ag / AgCl composite electrode is used as a reference electrode, and a bicarbonate solution is used as an electrolyte. CO2 is introduced into the electrolyte in the cathode area, and electricity is turned on to carry out the reaction.

[0045] As a specific implementation method, the CO2 conversion reaction is carried out in a vacuum reaction device, including the following steps: adding a dispersion containing the CO2 conversion catalyst and water into a closed vacuum reaction device, evacuating the device, heating to evaporate the water, and introducing CO2 to react; the dispersion is a mixture of the CO2 conversion catalyst, N-methyldiethanolamine and water. Specific embodiments The present invention is described below by specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Without departing from the spirit and scope of the inventive concept, changes and advantages that can be thought of by those skilled in the art are included in the present invention, and the attached claims and any equivalents thereof are the protection scope of the present invention.

[0047] Unless otherwise defined, all technical terms and scientific terms used in the present invention have the same meanings as those commonly understood by ordinary technicians in the field to which the present disclosure belongs. Unless otherwise specified, the raw materials and equipment used in the present invention are conventional raw materials and equipment in the field and can be obtained from conventional commercial channels; unless otherwise specified, the methods used in the present invention are conventional methods in the field.

[0048] The abbreviations used in the following examples, comparative examples and test examples have the following meanings: Ni@UiO-66: UiO-66 loaded with Ni nanoparticles; PTA: terephthalic acid; DMF: N,N-dimethylformamide; PVP: polyvinylpyrrolidone; CA, CA enzyme: carbonic anhydrase; FDH, FDH enzyme: formate dehydrogenase; MDEA: N-methyldiethanolamine.

[0049] Example 1: Preparation of CA / Ni@UiO-66 This embodiment provides a method for preparing a CO2 conversion catalyst, the steps are as follows: (1) Preparation of UiO-66: 33.4 mg ZrCl4 and 25 mg PTA were dissolved in 5 mL DMF, stirred at 25 ° C and 250 rpm for 60 min, and 0.7 mL formic acid was added and stirred for 30 min. The mixed solution was transferred to a reactor, sealed, and placed in an oven at 120 ° C for 24 hours. After natural cooling, the obtained product was centrifuged, the supernatant was removed, and the lower solid was washed three times with DMF, and then immersed in a methanol / water mixture (wherein the volume fraction of methanol was 99%) for 24 hours, centrifuged again, the supernatant was removed, and the lower solid was placed in a vacuum drying oven at 50 ° C for 12 hours to obtain UiO-66.

[0050] (2) Preparation of Ni@UiO-66: 250 mg Ni(NO3)2·6H2O was dissolved in 50 mL of double distilled water, and 200 mg UiO-66 was added after complete dissolution, ultrasonically dispersed and stirred for 12 hours at room temperature. Subsequently, the dispersed suspension was rotary evaporated at 65 ° C for 60 min to obtain a green solid powder. The solid powder was placed in a tubular furnace and heated to 300 ° C at a heating rate of 5 ° C / min under a nitrogen atmosphere and maintained for 5 hours. Then the gas was switched to a H2 / Ar mixed gas (wherein the volume fraction of H2 was 5%), and calcination was continued at 300 ° C for 5 hours to obtain Ni@UiO-66, in which the nickel loading was 20% (that is, the mass of Ni contained was 20% of the mass of Ni@UiO-66, and the "nickel loading" in each embodiment below has the same meaning).

[0051] (3) Enzyme solution preparation: Weigh 10 mg of CA enzyme powder, dissolve it in 0.5 mL of deionized water, add 0.5 mL of 10 mg / mL PVP aqueous solution, let stand for 30 min to obtain CA enzyme solution, and store it in a -80°C refrigerator for later use.

[0052] (4) Immobilization of CA enzyme: Add 20mL CA enzyme solution to a 50mL beaker, add 100mg Ni@UiO-66 powder, put it in a water bath, stir it at 25℃, 250rpm for 5min, centrifuge it at 4℃, 6500rpm for 20min after stirring, remove the supernatant, wash the lower solid with deionized water and centrifuge it, repeat three times to remove the residual reactants and CA enzyme. Put the lower solid into a vacuum drying oven and dry it at 30℃ for 12 hours to obtain a powdered CO2 conversion catalyst (CA / Ni@UiO-66). The enzyme loading rate is 20% (that is, in the CA enzyme used in this step, 20% is loaded on Ni@UiO-66, and the "enzyme loading rate" in each embodiment below has the same meaning), and the enzyme loading rate is calculated as follows:

[0053] Example 2: Preparation of CA / Ni@UiO-66 This embodiment provides a method for preparing a CO2 conversion catalyst, the steps are as follows: (1) Preparation of UiO-66: 33.4 mg ZrCl4 and 25 mg PTA were dissolved in 5 mL DMF, stirred at 25 ° C and 250 rpm for 60 min, and 0.7 mL formic acid was added and stirred for 30 min. The mixed solution was transferred to a reactor, sealed, and placed in an oven at 120 ° C for 24 hours. After natural cooling, the obtained product was centrifuged, the supernatant was removed, and the lower solid was washed three times with DMF, and then immersed in a methanol / water mixture (wherein the volume fraction of methanol was 99%) for 24 hours, centrifuged again, the supernatant was removed, and the lower solid was placed in a vacuum drying oven at 50 ° C for 12 hours to obtain UiO-66.

[0054] (2) Preparation of Ni@UiO-66: Dissolve 250mg Ni(NO3)2·6H2O in 50mL double distilled water, add 200mg UiO-66 after complete dissolution, ultrasonically disperse and continue stirring at room temperature for 10 hours. Subsequently, the dispersed suspension was rotary evaporated at 65°C for 60min to obtain a green solid powder. The solid powder was placed in a tubular furnace and heated to 300°C at a heating rate of 5°C / min under a nitrogen atmosphere and maintained for 5 hours. Then the gas was switched to a H2 / Ar mixed gas (where the volume fraction of H2 was 5%), and calcination was continued at 300°C for 5 hours to obtain Ni@UiO-66, with a nickel loading of 18.4%.

[0055] (3) Enzyme solution preparation: Weigh 10 mg of CA enzyme powder, dissolve it in 0.5 mL of deionized water, add 0.5 mL of 10 mg / mL PVP aqueous solution, let stand for 30 min to obtain CA enzyme solution, and store it in a -80°C refrigerator for later use.

[0056] (4) Immobilization of CA enzyme: Add 20mL CA enzyme solution and 100mg Ni@UiO-66 powder to a 50mL beaker, put it in a water bath, stir it at 25℃ and 250rpm for 5min, centrifuge it at 4℃ and 6500rpm for 25min after stirring, remove the supernatant, wash the lower solid with deionized water and centrifuge it, repeat three times to remove the residual reactants and CA enzyme. Put the lower solid into a vacuum drying oven and dry it at 30℃ for 12 hours to obtain a powdered CO2 conversion catalyst (CA / Ni@UiO-66). The enzyme loading rate is 22.5%.

[0057] Example 3: Preparation of CA / Ni@UiO-66 This embodiment provides a method for preparing a CO2 conversion catalyst, the steps are as follows: (1) Preparation of UiO-66: 33.4 mg ZrCl4 and 25 mg PTA were dissolved in 5 mL DMF, stirred at 25 ° C and 250 rpm for 60 min, and 0.7 mL formic acid was added and stirred for 30 min. The mixed solution was transferred to a reactor, sealed, and placed in an oven at 120 ° C for 24 hours. After natural cooling, the obtained product was centrifuged, the supernatant was removed, and the lower solid was washed three times with DMF, and then immersed in a methanol / water mixture (wherein the volume fraction of methanol was 99%) for 24 hours, centrifuged again, the supernatant was removed, and the lower solid was placed in a vacuum drying oven at 50 ° C for 12 hours to obtain UiO-66.

[0058] (2) Preparation of Ni@UiO-66: 250mg Ni(NO3)2·6H2O was dissolved in 50mL of double distilled water. After complete dissolution, 200mg UiO-66 was added, ultrasonically dispersed and stirred for 9 hours at room temperature. Subsequently, the dispersed suspension was rotary evaporated at 65°C for 60min to obtain a green solid powder. The solid powder was placed in a tubular furnace and heated to 300°C at a heating rate of 5°C / min under a nitrogen atmosphere and maintained for 5 hours. Then the gas was switched to a H2 / Ar mixed gas (where the volume fraction of H2 was 5%), and calcination was continued at 300°C for 5 hours to obtain Ni@UiO-66, with a nickel loading of 17%.

[0059] (3) Enzyme solution preparation: Weigh 10 mg of CA enzyme powder, dissolve it in 0.5 mL of deionized water, add 0.5 mL of 10 mg / mL PVP aqueous solution, let stand for 30 min to obtain CA enzyme solution, and store it in a -80°C refrigerator for later use.

[0060] (4) Immobilization of CA enzyme: Add 20mL CA enzyme solution and 100mg Ni@UiO-66 powder to a 50mL beaker, put it in a water bath, stir it at 25℃ and 250rpm for 5min, centrifuge it at 4℃ and 6500rpm for 27min after stirring, remove the supernatant, wash the lower solid with deionized water and centrifuge it, repeat three times to remove the residual reactants and CA enzyme. Put the lower solid into a vacuum drying oven and dry it at 30℃ for 12 hours to obtain a powdered CO2 conversion catalyst (CA / Ni@UiO-66). The enzyme loading rate is 24.5%.

[0061] Example 4: Preparation of CA / Ni@UiO-66 This embodiment provides a method for preparing a CO2 conversion catalyst, the steps are as follows: (1) Preparation of UiO-66: 33.4 mg ZrCl4 and 25 mg PTA were dissolved in 5 mL DMF, stirred at 25 ° C and 250 rpm for 60 min, and 0.7 mL formic acid was added and stirred for 30 min. The mixed solution was transferred to a reactor, sealed, and placed in an oven at 120 ° C for 24 hours. After natural cooling, the obtained product was centrifuged, the supernatant was removed, and the lower solid was washed three times with DMF, and then immersed in a methanol / water mixture (wherein the volume fraction of methanol was 99%) for 24 hours, centrifuged again, the supernatant was removed, and the lower solid was placed in a vacuum drying oven at 50 ° C for 12 hours to obtain UiO-66.

[0062] (2) Preparation of Ni@UiO-66: 250mg Ni(NO3)2·6H2O was dissolved in 50mL of double distilled water. After complete dissolution, 200mg UiO-66 was added, ultrasonically dispersed and stirred at room temperature for 8 hours. Subsequently, the dispersed suspension was rotary evaporated at 65°C for 60min to obtain a green solid powder. The solid powder was placed in a tubular furnace and heated to 300°C at a heating rate of 5°C / min under a nitrogen atmosphere and maintained for 5 hours. Then the gas was switched to a H2 / Ar mixed gas (where the volume fraction of H2 was 5%), and calcination was continued at 300°C for 5 hours to obtain Ni@UiO-66, with a nickel loading of 13%.

[0063] (3) Enzyme solution preparation: Weigh 10 mg of CA enzyme powder, dissolve it in 0.5 mL of deionized water, add 0.5 mL of 10 mg / mL PVP aqueous solution, let stand for 30 min to obtain CA enzyme solution, and store it in a -80°C refrigerator for later use.

[0064] (4) Immobilization of CA enzyme: Add 20mL CA enzyme solution and 100mg Ni@UiO-66 powder to a 50mL beaker, put it in a water bath, stir it at 25℃ and 250rpm for 5min, centrifuge it at 4℃ and 6500rpm for 30min after stirring, remove the supernatant, wash the lower solid with deionized water and centrifuge it, repeat three times to remove the residual reactants and CA enzyme. Put the lower solid into a vacuum drying oven and dry it at 30℃ for 12 hours to obtain a powdered CO2 conversion catalyst (CA / Ni@UiO-66). The enzyme loading rate is 30%.

[0065] Example 5: Preparation of CA / Ni@UiO-66 This embodiment provides a method for preparing a CO2 conversion catalyst, the steps are as follows: (1) Preparation of UiO-66: 33.4 mg ZrCl4 and 25 mg PTA were dissolved in 5 mL DMF, stirred at 25 ° C and 250 rpm for 60 min, and 0.7 mL formic acid was added and stirred for 30 min. The mixed solution was transferred to a reactor, sealed, and placed in an oven at 120 ° C for 24 hours. After natural cooling, the obtained product was centrifuged, the supernatant was removed, and the lower solid was washed three times with DMF, and then immersed in a methanol / water mixture (wherein the volume fraction of methanol was 99%) for 24 hours, centrifuged again, the supernatant was removed, and the lower solid was placed in a vacuum drying oven at 50 ° C for 12 hours to obtain UiO-66.

[0066] (2) Preparation of Ni@UiO-66: Dissolve 250mg Ni(NO3)2·6H2O in 50mL of double distilled water, add 200mg UiO-66 after complete dissolution, ultrasonically disperse and continue stirring at room temperature for 15 hours. Subsequently, the dispersed suspension was rotary evaporated at 65°C for 60min to obtain a green solid powder. The solid powder was placed in a tubular furnace and heated to 300°C at a heating rate of 5°C / min under a nitrogen atmosphere and maintained for 5 hours. Then the gas was switched to a H2 / Ar mixed gas (where the volume fraction of H2 was 5%), and calcination was continued at 300°C for 5 hours to obtain Ni@UiO-66, with a nickel loading of 23.1%.

[0067] (3) Enzyme solution preparation: Weigh 10 mg of CA enzyme powder, dissolve it in 0.5 mL of deionized water, add 0.5 mL of 10 mg / mL PVP aqueous solution, let stand for 30 min to obtain CA enzyme solution, and store it in a -80°C refrigerator for later use.

[0068] (4) Immobilization of CA enzyme: Add 20mL CA enzyme solution and 100mg Ni@UiO-66 powder to a 50mL beaker, put it in a water bath, stir it at 25℃ and 250rpm for 5min, centrifuge it at 4℃ and 6500rpm for 15min after stirring, remove the supernatant, wash the lower solid with deionized water and centrifuge it, repeat three times to remove the residual reactants and CA enzyme. Put the lower solid into a vacuum drying oven and dry it at 30℃ for 12 hours to obtain a powdered CO2 conversion catalyst (CA / Ni@UiO-66). The enzyme loading rate is 16%.

[0069] Comparative Example 1: Preparation of Ni@UiO-66 This comparative example provides a method for preparing a CO2 conversion catalyst, the steps are as follows: (1) Preparation of UiO-66: 33.4 mg ZrCl4 and 25 mg PTA were dissolved in 5 mL DMF, stirred at 25 ° C and 250 rpm for 60 min, and 0.7 mL formic acid was added and stirred for 30 min. The mixed solution was transferred to a reactor, sealed, and placed in an oven at 120 ° C for 24 hours. After natural cooling, the obtained product was centrifuged, the supernatant was removed, and the lower solid was washed three times with DMF, and then immersed in a methanol / water mixture (wherein the volume fraction of methanol was 99%) for 24 hours, centrifuged again, the supernatant was removed, and the lower solid was placed in a vacuum drying oven at 50 ° C for 12 hours to obtain UiO-66.

[0070] (2) Preparation of Ni@UiO-66: Dissolve 250mg Ni(NO3)2·6H2O in 50mL double distilled water, add 200mg UiO-66 after complete dissolution, ultrasonically disperse and continue stirring at room temperature for 12 hours. Subsequently, the dispersed suspension was rotary evaporated at 65°C for 60min to obtain a green solid powder. The solid powder was placed in a tubular furnace and heated to 300°C at a heating rate of 5°C / min under a nitrogen atmosphere and maintained for 5 hours. Then the gas was switched to a H2 / Ar mixed gas (where the volume fraction of H2 was 5%), and calcination was continued at 300°C for 5 hours to obtain Ni@UiO-66.

[0071] Comparative Example 2: Preparation of CA / Ni@MOF-808 This comparative example provides a method for preparing a CO2 conversion catalyst, the steps are as follows: (1) Preparation of MOF-808: 116.5 mg of zirconium chloride, 35 mg of trimesic acid and 2.8 mL of glacial acetic acid were mixed and dissolved in 5 mL of DMF, then placed in a preheated 135°C oven for reaction for 24 h and centrifuged. The precipitate obtained by centrifugation was washed with DMF and methanol respectively. The solid obtained after washing was vacuum dried at 60°C overnight.

[0072] (2) Preparation of Ni@MOF-808: Dissolve 250mg Ni(NO3)2·6H2O in 50mL double distilled water, add 200mg MOF-808 after complete dissolution, ultrasonically disperse and continue stirring at room temperature for 12 hours. Subsequently, the dispersed suspension was rotary evaporated at 65°C for 60min to obtain a green solid powder. The solid powder was placed in a tubular furnace and heated to 300°C at a heating rate of 5°C / min under a nitrogen atmosphere and maintained for 5 hours. Then the gas was switched to a H2 / Ar mixed gas (where the volume fraction of H2 was 5%), and calcination was continued at 300°C for 5 hours to obtain Ni@MOF-808.

[0073] (3) Enzyme solution preparation: Weigh 10 mg of CA enzyme powder, dissolve it in 0.5 mL of deionized water, add 0.5 mL of 10 mg / mL PVP aqueous solution, let stand for 30 min to obtain CA enzyme solution, and store it in a -80°C refrigerator for later use.

[0074] (4) Immobilization of CA enzyme: Add 20mL CA enzyme solution and 100mg Ni@MOF-808 powder to a 50mL beaker, put it in a water bath, stir it at 25℃ and 250rpm for 5min, centrifuge it at 4℃ and 6500rpm for 20min after stirring, remove the supernatant, wash the lower solid with deionized water and centrifuge it, repeat three times to remove the residual reactants and CA enzyme. Put the lower solid into a vacuum drying oven and dry it at 30℃ for 12 hours to obtain a powdered CO2 conversion catalyst (CA / Ni@MOF-808).

[0075] Comparative Example 3: Preparation of CA / Co@UiO-66 This comparative example provides a method for preparing a CO2 conversion catalyst, the steps are as follows: (1) Preparation of UiO-66: 33.4 mg ZrCl4 and 25 mg PTA were dissolved in 5 mL DMF, stirred at 25 ° C and 250 rpm for 60 min, and 0.7 mL formic acid was added and stirred for 30 min. The mixed solution was transferred to a reactor, sealed, and placed in an oven at 120 ° C for 24 hours. After natural cooling, the obtained product was centrifuged, the supernatant was removed, and the lower solid was washed three times with DMF, and then immersed in a methanol / water mixture (wherein the volume fraction of methanol was 99%) for 24 hours, centrifuged again, the supernatant was removed, and the lower solid was placed in a vacuum drying oven at 50 ° C for 12 hours to obtain UiO-66.

[0076] (2) Preparation of Co@UiO-66: 250mg (CH3COO)2Co·4H2O was dissolved in 50mL DMF, and 200mg UiO-66 was added after complete dissolution, ultrasonically dispersed and stirred at room temperature for 12 hours. Subsequently, the dispersed suspension was rotary evaporated at 65°C for 60min to obtain a green solid powder. The solid powder was placed in a tubular furnace and heated to 300°C at a heating rate of 5°C / min under a nitrogen atmosphere and maintained for 5 hours. Then the gas was switched to a H2 / Ar mixed gas (where the volume fraction of H2 was 5%), and calcination was continued at 300°C for 5 hours to obtain Co@UiO-66.

[0077] (3) Enzyme solution preparation: Weigh 10 mg of CA enzyme powder, dissolve it in 0.5 mL of deionized water, add 0.5 mL of 10 mg / mL PVP aqueous solution, let stand for 30 min to obtain CA enzyme solution, and store it in a -80°C refrigerator for later use.

[0078] (4) Immobilization of CA enzyme: Add 20mL CA enzyme solution and 100mg Co@UiO-66 powder to a 50mL beaker, put it in a water bath, stir it at 25℃ and 250rpm for 5min, centrifuge it at 4℃ and 6500rpm for 20min after stirring, remove the supernatant, wash the lower solid with deionized water and centrifuge it, repeat three times to remove the residual reactants and CA enzyme. Put the lower solid into a vacuum drying oven and dry it at 30℃ for 12 hours to obtain a powdered CO2 conversion catalyst (CA / Co@UiO-66).

[0079] Comparative Example 4: Preparation of FDH / Ni@UiO-66 This comparative example provides a method for preparing a CO2 conversion catalyst, the steps are as follows: (1) Preparation of UiO-66: 33.4 mg ZrCl4 and 25 mg PTA were dissolved in 5 mL DMF, stirred at 25 ° C and 250 rpm for 60 min, and 0.7 mL formic acid was added and stirred for 30 min. The mixed solution was transferred to a reactor, sealed, and placed in an oven at 120 ° C for 24 hours. After natural cooling, the obtained product was centrifuged, the supernatant was removed, and the lower solid was washed three times with DMF, and then immersed in a methanol / water mixture (wherein the volume fraction of methanol was 99%) for 24 hours, centrifuged again, the supernatant was removed, and the lower solid was placed in a vacuum drying oven at 50 ° C for 12 hours to obtain UiO-66.

[0080] (2) Preparation of Ni@UiO-66: Dissolve 250mg Ni(NO3)2·6H2O in 50mL double distilled water, add 200mg UiO-66 after complete dissolution, ultrasonically disperse and continue stirring at room temperature for 12 hours. Subsequently, the dispersed suspension was rotary evaporated at 65°C for 60min to obtain a green solid powder. The solid powder was placed in a tubular furnace and heated to 300°C at a heating rate of 5°C / min under a nitrogen atmosphere and maintained for 5 hours. Then the gas was switched to a H2 / Ar mixed gas (where the volume fraction of H2 was 5%), and calcination was continued at 300°C for 5 hours to obtain Ni@UiO-66.

[0081] (3) Enzyme solution preparation: Weigh 10 mg of FDH enzyme powder, dissolve it in 1 mL of phosphate buffer (pH=7.0, 0.05 mmol / L), let it stand for 30 min to obtain FDH enzyme solution, and store it in a -80°C refrigerator for later use.

[0082] (4) Immobilization of FDH enzyme: Add 20mL FDH enzyme solution and 100mg Ni@UiO-66 powder to a 50mL beaker, put it in a water bath, stir it at 25℃ and 250rpm for 5min, centrifuge it at 4℃ and 6500rpm for 20min after stirring, remove the supernatant, wash the lower solid with deionized water and centrifuge it, repeat three times to remove the residual reactants and E enzyme. Put the lower solid into a vacuum drying oven and dry it at 30℃ for 12 hours to obtain a powdered CO2 conversion catalyst (FDH / Ni@UiO-66).

[0083] Test Example 1: Loading of Ni and CA enzymes UiO-66 (prepared by the same method as UiO-66 in Example 1) and CA / Ni@UiO-66 prepared in Example 1 were characterized by infrared spectroscopy (FT-IR), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS), and thermogravimetric analysis was performed. The results are shown in Figure 1 to Figure 4 .according to Figure 1 to Figure 4 It can be seen that by adopting the method of the present invention, Ni and CA enzymes can be loaded onto UiO-66.

[0084] Test Example 2: Catalytic effect in CO2 hydrogenation reaction The CO2 conversion catalysts prepared according to the methods of Examples 1 to 5 and Comparative Examples 1 to 4, as well as Ni metal particles and M metal particles, were tested for their catalytic CO2 hydrogenation reaction effects. The specific method is as follows: Preparation method of cathode: weigh 1mg of metal (Ni or Co) CO2 conversion catalyst and add it to 9.5mL anhydrous ethanol, then add 0.5mL 5wt.% Nafion solution, mix and disperse by ultrasonic method for 30min to obtain a uniformly mixed catalyst ink. Use a micropipette to measure 5μL of catalyst ink and drop it on the surface of the clean glassy carbon electrode that has been polished with suede and alumina powder. Let it stand at room temperature and dry naturally before conducting electrochemical testing.

[0085] H-type electrolytic cell test: The performance test in the H-type electrolytic cell adopts the three-electrode system method, and its structure is as follows: Figure 5As shown. A glassy carbon electrode loaded with a CO2 conversion catalyst is placed in the cathode region of the electrolytic cell, a carbon rod is placed in the anode region, and the positive and negative electrodes are separated by a Nafion membrane. An Ag / AgCl reference electrode is placed in the cathode region. Electrolyte solution is injected into the positive and negative electrodes, and the cathode region is sealed, leaving an air inlet below the electrolyte surface and an air outlet above the electrolyte surface for ventilation and product detection.

[0086] A KHCO3 solution with a concentration of 0.5 mol / L was used as the electrolyte for the cathode and anode regions. Before the power-on test, CO2 gas was continuously introduced into the cathode electrolyte to saturate it, and CO2 was continuously introduced at a gas flow rate of 20 sccm and H2 at a gas flow rate of 40 sccm during the test. A constant working voltage was applied using an electrochemical workstation. After maintaining a certain voltage value for 10 minutes, the gas discharged from the cathode region was directly introduced into a gas chromatograph to detect the type and content of the product, and the current value of the electrochemical workstation during the injection was recorded. The current density corresponding to different overpotentials is shown in Table 1.

[0087] Table 1 Test results of the catalytic effect of CO2 hydrogenation reaction Analyzing the test results in Table 1, we can see that: (1) The efficiency of catalyzing the CO2 hydrogenation reaction in Example 1 is higher than that in Comparative Example 1 and Comparative Example 4. This indicates that loading CA enzyme on Ni@UiO-66 can improve its efficiency in catalyzing the CO2 hydrogenation reaction, and not all CO2 immobilization enzymes can produce this effect.

[0088] (2) Example 1 has a higher efficiency in catalyzing CO2 hydrogenation reaction than Ni nanoparticles and Comparative Example 2; when used alone, Co nanoparticles have a slightly higher efficiency in catalyzing CO2 hydrogenation reaction than Ni nanoparticles, but after being loaded on UiO-66, Comparative Example 3 has a lower efficiency in catalyzing CO2 hydrogenation reaction than Example 1. This indicates that loading the chemical catalyst Ni on UiO-66 can improve its efficiency in catalyzing CO2 hydrogenation reaction, and this improvement effect is affected by the types of MOF and chemical catalyst, because the interaction between Ni and UiO-66 can improve the catalytic effect of the catalyst in the CO2 hydrogenation reaction.

[0089] (3) The efficiency of catalyzing the CO2 hydrogenation reaction in Examples 1 to 3 is higher than that in Examples 4 and 5. This indicates that in the CO2 conversion catalyst of the present invention, the ratio between the CA enzyme and the Ni nanoparticles will affect the CO2 hydrogenation reaction efficiency. When the ratio is too large or too small, the CO2 hydrogenation reaction efficiency will decrease.

[0090] Test Example 3: Catalytic effect in CO2 hydration reaction The CO2 conversion catalyst (CA / Ni@UiO-66) prepared according to the method in Example 1, as well as UiO-66 (preparation method is the same as UiO-66 in Example 1) and CA enzyme were taken, and the activity of each catalyst in catalyzing the CO2 hydration reaction was tested by pressure measurement using a micro vacuum reactor. The whole test system consists of a micro vacuum reactor 1, a magnetic stirrer 2, an outlet valve 3, an inlet valve 4, a vacuum pressure sensor 5, a vacuum pump 6, a high-purity carbon dioxide cylinder 7, a magnetic heating stirrer 8 and a computer 9. The specific structure is shown in Figure 6 , the test method is as follows: Add 20mL 1mol / L N-methyldiethanolamine (MDEA) solution and a catalyst containing 1mg CA enzyme into the reactor. After sealing, use a vacuum pump to extract the air from the top of the reactor through the outlet valve, and then place the reactor in a magnetic stirring water bath at 40°C and 200rpm. As the temperature in the reactor rises, the water evaporates, and the internal pressure gradually rises to a stable state. At this time, the pressure in the reactor can be regarded as the saturated vapor pressure of water at 40°C. Open the air inlet valve and pass CO2 until the CO2 partial pressure in the reactor is 15kPa, then close the air inlet valve. As the CO2 in the reactor is absorbed by the solution, the air pressure gradually decreases. The computer automatically records the pressure changes. After the reaction is completed, the top air is extracted, CO2 is passed, and the experiment is repeated. The average of the three experimental results is taken as the final result. The calculation formula for relative activity (Relative Activity) is as follows:

[0091] The activity test results of UiO-66, free CA enzyme and CA / Ni@UiO-66 catalyzing CO2 hydration reaction are shown in Figure 7 It can be seen that after loading CA enzyme onto Ni@UiO-66, the efficiency of CA enzyme catalyzing CO2 hydration reaction can be effectively improved.

[0092] The catalytic activities of UiO-66, free CA enzyme and CA / Ni@UiO-66 in CO2 hydration reaction were measured after they were stored in MDEA solution at 40℃ for 0 to 20 days. Figure 8 After CA / Ni@UiO-66 was used in CO2 hydration reaction for 1 to 6 times, the activity of catalytic CO2 hydration reaction was measured. Fig. 9 .from Figure 8 and Fig. 9 It can be seen that the CA / Ni@UiO-66 of the present invention has good long-term stability and reusability, and can still maintain a good catalytic effect of CO2 hydration reaction after long-term storage and repeated use.

[0093] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A CO2 conversion catalyst, characterized in that: The invention comprises a UiO-66 metal organic framework; the UiO-66 metal organic framework is loaded with Ni nanoparticles and carbonic anhydrase.

2. The CO2 conversion catalyst according to claim 1, characterized in that In the CO2 conversion catalyst, the loading amount of Ni nanoparticles is 15-20%, and the mass ratio of Ni nanoparticles to carbonic anhydrase is 1:2.0-2.

9.

3. A method for preparing the CO2 conversion catalyst according to claim 1 or 2, characterized in that: The following steps are involved: I: dissolving nickel salt in water, adding UiO-66 metal organic framework, combining, evaporating to remove water, and then reducing nickel ions to Ni to obtain UiO-66 loaded with Ni; II: Mix carbonic anhydrase, polyvinyl pyrrolidone and water to obtain enzyme solution, add the product of step I, combine them, and then separate the product.

4. The preparation method according to claim 3, characterized in that: In step I, the specific process of reducing nickel ions to Ni includes: heating to 300-320°C at a rate of 4-6°C in an inert gas atmosphere and maintaining for 4.5-5 h, then introducing a reducing gas containing hydrogen, and continuing to calcine at 250-300°C for 5-5.5 h.

5. The preparation method according to claim 3, characterized in that: In step II, in the enzyme solution, the concentration of carbonic anhydrase is 10-15 mg / mL, and the concentration of polyvinyl pyrrolidone is 5-10 mg / mL.

6. The preparation method according to claim 3, characterized in that: In step I, the combining method is stirring for 10 to 15 hours; in step II, the combining method is stirring for 5 to 10 minutes.

7. The preparation method according to claim 3, characterized in that: In step I, the preparation step of the UiO-66 metal organic framework includes: dissolving a zirconium salt and terephthalic acid in a solvent, stirring at 20-30° C. for 1-1.5 h, adding formic acid, continuing to stir for 0.5-1 h, reacting at 115-125° C. for 20-30 h, and separating the product; the mass volume ratio of the zirconium salt, terephthalic acid and formic acid is 1 g: 0.5-0.8 g: 100-150 mL.

8. The use of the CO2 conversion catalyst according to claim 1 or 2 in a CO2 conversion reaction, characterized in that: Products of the CO2 conversion reaction include methanol and carbonic acid.

9. The use according to claim 8, characterized in that: The CO2 conversion reaction is carried out in an electrolysis device, including the following steps: in the electrolysis device, a glass slide or carbon rod electrode is used as an anode, a glassy carbon electrode containing the CO2 conversion catalyst is used as a cathode, an Ag / AgCl composite electrode is used as a reference electrode, a bicarbonate solution is used as an electrolyte, CO2 is introduced into the electrolyte in the cathode area, and electricity is turned on to carry out the reaction.

10. The use according to claim 8, characterized in that: The CO2 conversion reaction is carried out in a vacuum reaction device, including the following steps: adding a dispersion containing the CO2 conversion catalyst and water into a closed vacuum reaction device, evacuating the device, heating to evaporate water, and introducing CO2 to react.